Speech perception of children with cochlear implants and children with traditional hearing aids - Mildner, Vesna (Array, 2006)
The aim of the study was to analyse speech perception of children with cochlear implants (N=29) and children fitted with traditional hearing aids (N=20). One- and two-syllable words were presented auditorily in a forced choice minimal-pair discrimination task. The children repeated the word and pointed to the appropriate picture presented on computer screen. The words were minimal pairs with respect to voicing or place of articulation in stops and fircatives ; among affricates the miminal pairs included the most frequently substituted fricatives and stops in addition to voicing and place of articulation. Vowel discrimination was tested in minimal pairs and in nonsense words differing only in the vowel. Unaided, all children were profoundly hearing impaired and were included in auditory-oral therapy (Verbotonal method). The smallest differences between the groups were found for stops and vowels, and the largest for fircatives and affricates. The implanted children were significantly more successful.